2014
DOI: 10.2516/ogst/2013188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Treatment and Physical Aging on the Gas Transport Properties in Matrimid®

Abstract: -Carbon dioxide and methane transport in a commercial polyimide, Matrimid 5218 Ò , has been characterized in order to evaluate the effect of membrane thermal treatment and physical aging on its potentialities for CO 2 /CH 4 separation. In particular, CO 2 and CH 4 permeabilities and diffusion coefficients were measured at three different temperatures (35, 45 and 55°C) in films pretreated at 50, 100, 150 and 200°C, respectively. The performances of each sample were examined for a period of more than 3 000 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 71 publications
(120 reference statements)
0
20
0
Order By: Relevance
“…As often showed by many authors, the polymer thermal history can significantly affect the mass transport properties, as well as the performance of glassy polymer membranes [7,9,40]. However, it was observed that the pretreatment of Matrimid s films at 200 1C is able to produce membranes with gas transport properties stable for a period of at least 6 months, as no significant aging was detected from gas permeability measurements [41]. Density measurements have been carried out on Matrimid s samples after the thermal pretreatment, by means of the buoyancy method (Sartorius Density Kit YDK01), weighing the specimens in air and in n-dodecane (Sigma-Aldrich, anhydrous, Z99% purity).…”
Section: Methodsmentioning
confidence: 75%
“…As often showed by many authors, the polymer thermal history can significantly affect the mass transport properties, as well as the performance of glassy polymer membranes [7,9,40]. However, it was observed that the pretreatment of Matrimid s films at 200 1C is able to produce membranes with gas transport properties stable for a period of at least 6 months, as no significant aging was detected from gas permeability measurements [41]. Density measurements have been carried out on Matrimid s samples after the thermal pretreatment, by means of the buoyancy method (Sartorius Density Kit YDK01), weighing the specimens in air and in n-dodecane (Sigma-Aldrich, anhydrous, Z99% purity).…”
Section: Methodsmentioning
confidence: 75%
“…the protocol used for preparation [6], the exposition to swelling agents [11], [12] or thermal treatments [13]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…vacuum at 200°C for 24 h prior to testing in order to ensure solvent and low molecular weight species removal, as well as to give stability to the membrane properties, because such pre-treatment ensures the absence of aging phenomena, that cause permeability to change with time, as proven in the case of Matrimid [13]. …”
mentioning
confidence: 98%
“…Although it is commonly acknowledged that gas transport properties of polymers are highly dependent on the polymer amorphous or semicrystalline microstructure, their relation with physical ageing has been much less studied. The importance of this parameter on gas transport properties has been mainly investigated on amorphous thin films usually prepared by solvent cast process from polymers with high glass transition temperature . The gas permeability of these films has been shown to change in time, due to a slow reorganization of the polymer chains from a nonequilibrium thermodynamical state to an equilibrium state, leading to a redistribution of the free volume sizes and contents.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this parameter on gas transport properties has been mainly investigated on amorphous thin films usually prepared by solvent cast process from polymers with high glass transition temperature. [20][21][22] The gas permeability of these films has been shown to change in time, due to a slow reorganization of the polymer chains from a nonequilibrium thermodynamical state to an equilibrium state, leading to a redistribution of the free volume sizes and contents. Film forming processes based on melt routes usually involve high cooling rates that can also lead to immobilize polymer chains in a non-equilibrium state.…”
mentioning
confidence: 99%